Novel Combination of Periodontal Ligament Stem Cells (PDLSCs)-Conditioned Medium and Taurine Increase Apoptosis in U87Glioma Tumor Cells: Possible Relevance to Glioblastoma Treatment - Masoumeh Einabadi; Jafar Ai; Hooshang Jamali; Mohammad Kargar; Farshid Kafilzadeh (Fasa University of Medical Sciences, 2021)
Background & Objective: Glioblastoma Multiforme is a very aggressive primary brain cancer that has a median overall survival even if the treatment period is less than 1 year. Despite progress in glioblastoma diagnosis and treatment, the prognosis of patients with glioblastoma still remains poor. Recently, it has been detected that stem cell therapies are an effective method for brain tumor cell targeting. Also, the anti-inflammatory and anti-apoptotic activity of taurine against cancerous cells has been found. Materials & Methods: In this study, we employed taurine as an anti-cancer drug and PDLSCs as a potential agent for improving anti-cancer drug efficiency. Then, we investigated their effect on the glioma tumor cells in in-vitro 2D cell culture and in vivo. Results: Taurine had the best apoptotic activity on the C6 glioblastoma cells at the concentration of 80 μM after 72h post-treatment. The obtained results showed that a combination of taurine/PDLSCs induced the expression of caspase-3, caspase-8, and IL-17Ra and down-regulated the expression of Bcl-2 and IL-17Ra. Uses of taurine and PDLSCs suppress the migration of the cancerous C6 cells after 48h and show good potential in the suppression of GBM metastasis. Conclusion: The taurine at concentration of 80µM has a strong potential in decreasing the viability of cancerous C6 Glioblastoma cells. Therefore, taurine and PDLSCs combination, due its therapeutic efficacy, has a considerable potential to be a successful method to glioblastoma brain cancer treatment.